From Caristi's Theorem to Ekeland's Variational Principle in 0σ-Complete Metric-Like Spaces. (28th August 2014) - Jleli, Mohamed; Samet, Bessem; Vetro, Calogero; Vetro, Francesca
Abstract : We discuss the extension of some fundamental results in nonlinear analysis to the setting of0 σ -complete metric-like spaces. Then, we show that these extensions can be obtained via the corresponding results in standard metric spaces.